Distributive Politics and Manipulative Policy in Local Election - Hermawan, Dedy; Kurniawan, Robi Cahyadi (Political Science Program, Universitas Negeri Semarang, 2019)
Distributive politics is part of the concept of patronage or clientelism, term of clientelism commonly referred to in some scientific literature. Research on distributive politics in the context of local politics, especially in the election of regional heads is still rare. Previous studies are still conducted within the national scope, such as presidential and legislative elections. This research tries to answer the question of how the process of distributive politics and manipulative policies runs in the local context of Bandar Lampung Local Election in 2015.The study was conducted in Bandar Lampung City in September 2016 until January 2017. This research used qualitative method through in-depth interview approach to informants related to the research. The informant consisted of several political actors, Herman HN's successful team and academics. The result of this research indicates that politics of distributive among voters occurs in the selection of Bandar Lampung Mayor. There is a symbiotic mutualism between candidate and the voters in Bandar Lampung Local Election. Voters can be influenced by the choice of imaging of candidate, through the concept of distributive politics or pork barrels politics or provide necessary needs for the voting community with infrastructure policy; roads and bridges, free education, free health and religious social assistance. Other results indicate that the manipulative policies carried out by candidate make voters lulled to absurd performance that ends in the Bandar Lampung City budget crisis after the policy is rolled out.